Resource-Rich Yet Malnourished: Analysis of the demand for food nutrients in the Democratic Republic of Congo - Ulimwengu, John M.; Roberts, Cleophelia; Randriamamonjy, Josee (International Food Policy Research Institute, 2012)
Endowed with 80 million hectares of arable land (of which only 10 percent are used), diverse climatic conditions, and abundant water resources, the Democratic Republic of Congo (DRC) has the potential to become the breadbasket of the entire African continent. Instead, the country is one of the most affected by malnutrition. The DRC has the highest number of undernourished persons in Africa and the highest prevalence of malnutrition in the world. As a result, child stunting and infant mortality rates in the DRC are also among the highest in the world. Overall, at least 50 percent of the population is deficient in vitamin B12, calories, riboflavin, iron, vitamin E, folate, and zinc; vitamins A, C, and B6, for which palm oil and cassava are the main sources, are generally consumed in sufficient quantities. Across provinces, there is significant heterogeneity. All nutrients exhibit positive expenditure elasticities in both rural and urban areas; however, as expected, the expenditure elasticities of all nutrients are higher in urban areas than in rural areas. In rural areas, strategies to improve nutrition will need to use instruments that attack malnutrition directly rather than relying simply on rising incomes. With respect to prices, an increase in own price is expected to have a nonpositive effect on all nutrients. Our results also suggest significant substitution effects. Overall, our results highlight the paradox of the DRC, a country with huge potential for agricultural development but incapable of feeding itself in terms of both quantity and quality of nutrients.